PENGGUNAAN AKRUAL UNTUK PERATAAN LABA - INDRA WIJAYA KUSUMA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2004)
The use of discretionary accruals for the purpose of income increasing or income decreasing has been examined widely. However, als for the purpose of income smoothing has not been accounting research. Most studies concerning income smoothing is on the factors that affect the probability the company to smooth income. The purpose of this study is to examine whether income smoother uses discretionary accruals to accomplish the purpose. Specifically, this study investigates whether the discretionary accruals are used when the company financial performance is good. The sample consists of 85 listed companies in the Jakarta Stock Exchange. The sample are not from service nor financial institutions, such as banks, insurance, and investment companies since they have different characteristics than the manufacturing. The data are taken from the year 1997 to 2001. The result shows that income smoothing does not correlate with the discretionary accruals. Therefore, the smoothers do not use discretionary accruals to achieve their purpose. Another result shows that smoothers who have good performance have lower discretionary accruals than those who do not have good performance. This result contradicts the logic that smoothers will have more discretionary accruals to achieve their purpose of income smoothing. The logical explanation of this result is that non-performing companies try to cover their performance by using higher discretionary accruals, especially in the period of crisis. Future research are needed to refine this study, especially in the using of Eckel index to categorize smoothers and non smoothers. Another possibility is to use longer period data to avoid the bias from the in crisis in the 1997 or to compare the results using data before versus after 1997 monetary crisis.